Understanding broad-spectrum disease resistance in rice: prompting a genome-wide uprising - Tonnessen, Bradley William, author; Leach, Jan E., advisor; Ben-Hur, Asa, committee member; Jahn, Courtney E., committee member; Argueso, Cristiana T., committee member; Bush, Daniel R., committee member (Colorado State University. Libraries, 2017)
Rice is the main staple food crop of the world, and thus, the detriments caused by rice diseases are a threat to international food security. The emergence of new virulent strains of pathogens can significantly reduce yields, and there are continual efforts to develop more resistant rice cultivars. Utilization of single R-genes is effective, but has proven inadequate due to rapid pathogen evolution. Thus, there is a need for breeding multigenic, broad-spectrum disease resistance in new varieties. This study aims to understand the aspects of basal resistance and its contribution to tolerance to multiple, diverse pathogens. Phenylalanine ammonia-lyase is a key enzyme in phenylpropanoid metabolism, which contributes to the basal defense response (DR). In this project, the DR gene, OsPAL4, which colocalizes with a disease resistance Quantitative Trait Loci (QTL), was shown to contribute to resistance to three important rice diseases, rice blast, bacterial blight, and sheath blight, in experiments using an ospal4 mutant. The functional element of resistance QTL haplotypes of DR genes such as OsPAL4 are largely unknown, and this work searched for sequence patterns in the promoters of DR genes to discern a regulatory mechanism specific to DR. Multiple cis-regulatory Modules (CRMs), or groups of DR-related sequence motifs were identified in promoters of DR genes. These CRMs harbor structural organizations of cis-elements known to be involved in the DR, and also motifs involved in a putative epigenetic regulatory mechanism. Polymorhpisms in CRMs are found in resistant relative to susceptible QTL haplotypes in DR gene promoters. These CRMs are sequence patterns found across DR gene promoters. Thus, we hypothesize that DR-associated CRM can be used as breeding markers to select loci on a genome scale that encode traits supporting broad spectrum basal resistance to important rice diseases.
Zip file contains table legend and supplementary tables.